2000
DOI: 10.1007/s001980050289
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound and Bone Mineral Density in Patients with Primary Hyperparathyroidism Before and after Surgical Treatment

Abstract: The aim of this study was to assess the pattern of ultrasound (QUS) parameters and bone mineral density at different skeletal sites in patients with primary hyperparathyroidism (PHPT) before and after surgical treatment. In 22 patients (age range 28-74 years) with PHPT we measured speed of sound (SOS), attenuation (BUA) and Stiffness at the calcaneus, amplitude-dependent speed of sound (AD-SoS) at proximal phalanges, and bone mineral density at lumbar spine (BMD-LS) and at the mid-radius (BMD-MR) and ultra-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
2
22
1
5
Order By: Relevance
“…SOS in the calcaneus increased too, but only the difference between present and baseline measurements was significant, since the difference between the present and the last measurement (5 years ago) was not. Our results of greater response of SOS in the phalanges than in the calcaneus are similar to those reported by other authors [3]. The BUA value decreased (not significant according to LSC) in comparison to the last measurement, and SI remained the same, although they both were higher than baseline results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SOS in the calcaneus increased too, but only the difference between present and baseline measurements was significant, since the difference between the present and the last measurement (5 years ago) was not. Our results of greater response of SOS in the phalanges than in the calcaneus are similar to those reported by other authors [3]. The BUA value decreased (not significant according to LSC) in comparison to the last measurement, and SI remained the same, although they both were higher than baseline results.…”
Section: Discussionsupporting
confidence: 92%
“…Quantitative ultrasound (QUS) is a widely accepted method for the diagnosis of skeletal status in postmenopausal osteoporosis and different metabolic bone diseases [2]. There are several studies on QUS measurements in patients with PHPT [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, bone density increases. Recent long-term data on the course of treated and untreated asymptomatic primary hyperparathyroidism have confirmed that successful surgery leads to sustained increases in bone mineral density at sites rich in cancellous bone such as the lumbar spine, where a mean rise of 12% in bone mass is seen after parathyroidectomy (8,21,41,42). In line with this increase in bone density, there is preliminary (case-control) evidence to suggest that surgery might reduce the risk of subsequent fracture (43).…”
Section: Management Of Primary Hyperparathyroidism -Treating Older Pamentioning
confidence: 93%
“…The ability of ultrasound measurements to detect bone growth and ageing and to assess fracture risk in various metabolic bone diseases was presented in a review [10]. Among other studies, phalangeal ultrasound measurements were also used in the detection of various hormonal disorders [11,12]. There are differences among studied populations, and there is no available data on ultrasound measurements of phalangeal bones in healthy adolescents of the Lower Silesia region.…”
Section: Introductionmentioning
confidence: 99%